THE WORK ENVIRONMENTAL RELATIONSHIP AND WORK MOTIVATION ON THE PERFORMANCE OF EMPLOYEES OF KOPERASI MAKMUR MANDIRI - Fetrando, Fetrando Sakti Kasih Harahap; Suzanna Josephine L.Tobing; Ganda Hutapea (Buletin Ekonomi, 2024)
Study was compiled by FETRANDO SAKTI KASIH HARAHAP with the title "WORK ENVIRONMENT AND WORK MOTIVATION ON THE PERFORMANCE OF EMPLOYEES KOPERASI MAKMUR MANDIRI" This research study was completed after carrying out a 2-month study at the selected location. The purpose of the researchers conducting this study is to facilitate problem solving in the Makmur Mandiri Cooperative related to employees. This research study was conducted to find information related to the state of the work environment and work motivation to produce employee performance at the Makmur Mandiri Cooperative. The data in this research study were collected using a questionnaire. The deductive method and the inductive method are the methods used to write this study. The Makmur Mandiri Cooperative is the location for the researchers to carry out this study. The findings of this research study are that there is a significant relationship between work environment and work motivation on employee performance in the Makmur Mandiri Cooperative. Employee performance at the Makmur Mandiri Cooperative can increase the quality and profits of its business. Keywords: Work Environment, Work Motivation, Employee Performance, Makmur Mandiri Cooperative.